Epidemiological profile of people living with HIV-AIDS: a challenge social (Research, Society and Development, 2021)
Acquired immunodeficiency syndrome (AIDS) is an advanced clinical manifestation resulting from an immunodeficiency condition caused by human immunodeficiency virus (HIV), which is transmitted by the sexual, parenteral or vertical routes. (UNAIDS. AIDS epidemic update; 2007). HIV alters the cell's DNA, creates an infection cycle in which it continually multiplies, making it a chronic and potentially lethal pathology (Brasil, 2020). To contain the epidemic of disease, it is strictly necessary to monitor and treat infected patients. Therefore, from this article, a descriptive cross-sectional study was carried out, based on data from SINAN (Information System for Notifiable Diseases), available at DATASUS, between the periods 2010 and 2020, in which the objective was to verify the profile epidemiological study of people living with HIV-AIDS in the city of Vitória da Conquista, and verifying the effects of the stigmatization of disease, prejudice and, more recently, the pandemic caused by Covid-19 virus. From collected data, about 59.81% of patients were male and 56.12% female. Most diagnosed cases were young people aged 18 to 28 years old. Regarding notifications, they have remained unstable until the year 2019, in a total of about 24,000 to 25,000 notified cases. In 2020, there was a drop, with 8,434 reported cases. In relation to race, the research points to an increase in the number of AIDS cases among blacks and browns for both sexes; blacks were about 3,000 in 2008, passing through 1,915 in 2019, declining to 541 cases. The browns, on the other hand, at around 9,000 thousand, in 2008, dropping to 2,474, in 2020, while among whites they pointed to a proportional reduction. Therefore, the study concludes that social issues and other external factors reflect on the profile of patients infected with the HIV virus, as well as causing changes in disease rates in the city of Vitória da Conquista.